أذر امػومىث غنى امدومث في امشرق األوسط وطنع امقرن امحادي وامػشرًي - األسخاذ امىساغد امدكخور كىال غتداهلل امجاف (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The countries in the Middle East Although have undergone various political changes and developments, they have not benefited from any of them. The political dilemmas on the internal and external levels have remained in place and have not interacted positively with them, but with all political or perhaps economic changes. To a kind of crisis and non-adaptation and interaction with them, because the political regimes in the Middle East is not the present reality of these nations and could not integrate them with the interests of peoples. But the peoples have repeatedly tried to escape themselves from those corrupt and unjust political systems, but political equations do not do what they desire. The crisis of the state is a crisis of performance and keeping pace. It is a crisis of performance in deviating from the path of the state / nation as a result of the institutionalization of institutions. Due to the rigidity of the first and growing second changes. The region needs a new social and political contract that regulates the relationship between the state and the society to solve the crises experienced by the state, the political system and the society in order to ensure the survival of the state and social peace through dialogue and comprehensive reconciliation with a view to the comprehensive reform of the political system and the rebuilding of the state. Globalization is an inevitable reality. We are collectively subject to its new laws imposed by the progress of globalization on all groups and societies. It is necessary to deal with them from within and engage in the global process provided that a distinct strategy of nationalism is developed to benefit from its potential.